2019
DOI: 10.1021/acsaelm.9b00748
|View full text |Cite
|
Sign up to set email alerts
|

Full Activation of Boron in Silicon Doped by Self-Assembled Molecular Monolayers

Abstract: Self-assembled molecular monolayer (SAMM) doping has great potential in state-of-the-art nanoelectronics with unique features of atomically precision and nondestructive doping on complex 3D surfaces. However, it was recently found that carbon impurities introduced by the SAMM significantly reduced the activation rate of phosphorus dopants by forming majority carrier traps. Developing a defect-free SAMM-doping technique with a high activation rate for dopants becomes critical for reliable applications. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This opens a pathway for using on-surface solvothermal chemistry as a process for directly introducing dopants in future electronic devices. As the adventitious chemistry from this demonstration may ultimately hinder electrical investigation, [18] our results also demonstrate the continued need for knowledgeable synthetic chemists to adapt existing chemical processes into surface reactions.…”
mentioning
confidence: 66%
“…This opens a pathway for using on-surface solvothermal chemistry as a process for directly introducing dopants in future electronic devices. As the adventitious chemistry from this demonstration may ultimately hinder electrical investigation, [18] our results also demonstrate the continued need for knowledgeable synthetic chemists to adapt existing chemical processes into surface reactions.…”
mentioning
confidence: 66%
“…The diversity of organic molecules and the flexibility of self-assembly process make MLD an attractive and controllable doping technique. Dopants including phosphorus [20][21][22][23][24][25][26][27][28][29][30], boron [8,20,[31][32][33][34], nitrogen [35], arsenic [27,36] and antimony [37] have been introduced to silicon by MLD using commercial or synthetic reagents.…”
Section: Molecular Monolayer Dopingmentioning
confidence: 99%
“…While carbon impurities have significant influence on the activation of phosphorus dopant, recent research reveals that they have limited impact on boron-doped samples via MLD [32]. Investigated by DLTS and minority carrier transient spectroscopy, Gao et al [32,34] found that carbon-related defects are in form of C s H and C s OH, which act as minority carrier traps. The majority carrier traps were found in form of B s -O 2i , which exist at a low level (less than 1%) and can be potentially suppressed by carbon impurities.…”
Section: Molecular Monolayer Dopingmentioning
confidence: 99%
“…However, we recently found that carbon impurities of the dopant carrying molecules were driven into the silicon lattice along with the dopant atoms, partially or seriously deactivate the electrical activity of phosphorus dopant atoms depending on the doping concentrations, ,, although carbon impurities in p-type Si form minority traps and have a limited impact on acceptor-type dopants . It is thus important to develop a carbon-free SAMM doping technology, which has been explored in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…9−11 However, we recently found that carbon impurities of the dopant carrying molecules were driven into the silicon lattice along with the dopant atoms, partially or seriously deactivate the electrical activity of phosphorus dopant atoms depending on the doping concentrations, 9,12,13 although carbon impurities in p-type Si form minority traps and have a limited impact on acceptor-type dopants. 14 It is thus important to develop a carbon-free SAMM doping technology, which has been explored in recent years. To avoid the introduction of carbon impurities into the substrate, Longo et al 15,16 and Zhi et al 17 used low temperature pyrolysis to break the P−C bond at 500 °C before high temperature annealing treatment and then released the alkane chain in the octadecylphoshponic acid (ODPA) molecule.…”
Section: ■ Introductionmentioning
confidence: 99%